Starting triathlon - Barfield, Mark (The Crowood Press Ltd, 2006)
It is a truism that the sport of triathlon is both very challenging and incredibly rewarding. This work is aimed at those who are considering becoming triathletes and those who have recently taken up the sport. It helps novice triathletes learn how to train and prepare for race day